2018
DOI: 10.1159/000491977
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of T Lymphocyte Subsets in Immune Thrombocytopenia Associated with Anti-GPIIb/IIIa- and/or Anti-GPIbα-Mediated Responses Are Differentially Sensitive to Dexamethasone

Abstract: Objective: The aim of this work was to investigate the influence of T lymphocyte subsets and platelet-specific autoantibodies on immune thrombocytopenia (ITP) with dexamethasone therapy. Methods: The samples were obtained from patients before therapy. T lymphocyte subsets were measured by flow cytometry, and platelet-specific autoantibodies were evaluated by modified monoclonal antibody immobilization of platelet antigen assay. Results: A total of 50 ITP patients were involved in the study. Twenty-three were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Studies on adult affect clinical prognosis and that the presence of anti‐GPIb/IX autoantibodies is a predictive factor for poor prognosis risk . In accordance with data from animal models, a recent study suggested ITP patients who were anti‐GPIbα antibody positive were insensitive to dexamethasone treatment . However, there has been no relevant study in children.…”
Section: Introductionmentioning
confidence: 97%
“…Studies on adult affect clinical prognosis and that the presence of anti‐GPIb/IX autoantibodies is a predictive factor for poor prognosis risk . In accordance with data from animal models, a recent study suggested ITP patients who were anti‐GPIbα antibody positive were insensitive to dexamethasone treatment . However, there has been no relevant study in children.…”
Section: Introductionmentioning
confidence: 97%
“…After taking prednisone for a long time, the platelet count remained low until 4th June 2020, therefore, we highly suspected that the patient had a secondary ITP caused by SARS-CoV-2 infection. Lymphocytes and subsets play a vital role in the maintenance of immune system [ 9 ]. The decrease of the lymphocyte and subsets, especially the CD4+ T cells, CD8+ T cells and NK (CD56+) cells was significant, indicating an impairment of the immune system caused by SARS-CoV-2 infection, which might trigger an autoimmune response [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the continuous thrombocytopenia in this case was due to immune dysregulation, especially the T cells, such as CD4+ T cells and CD8+ T cells, which was important for the immune system. As reported in the previous studies, T cells play a vital role in immune system and may affect the effective of glucocorticoid on the thrombocytopenia [ 9 ]. We defined the degree of severity of Covid-19 at the time admission according to the seventh Trial Version of the Novel Coronavirus Pneumonia Diagnosis and Treatment Guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Immune thrombocytopenia (ITP) is a multifactorial autoimmune disorder characterized by antibody-mediated platelet destruction [1,2,3]. Impairments of T-cells and macrophages, together with a cytokine imbalance, have been recognized as key processes, although the pathogenesis remains unclear [4,5,6,7]. However, there is an increasing interest in MSC involvement in ITP pathogenesis [11] due to its important role in immune modulatory functions [8,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of the immune system and the heterogeneity of the disease, the pathogenesis of ITP remains unclear [4]. However, ITP is characterized by several aberrations such as the production of platelet autoantibodies, polarization of macrophages towards the M1 phenotype, an elevated Th1/Th2 ratio, and alteration of circulating cytokine profile [5,6,7]. Recent evidences suggest that mesenchymal stromal cells (MSCs) could also be involved in ITP pathogenesis [8].…”
Section: Introductionmentioning
confidence: 99%